Improvement of Surface Properties of Inconel718 by HVOF Coating with WC-Metal Powder and by Laser Heat Treatment of the Coating - Hui Gon Chun; Tong Yul Cho; Jae Hong Yoon; Gun Hwan Lee (Advances in Materials Science and Engineering)
High-velocity oxygen-fuel (HVOF) thermal spray coating with WC-metal powder was carried out by using optimal coating process on an Inconel718 surface for improvement of the surface properties, friction, wear, and corrosion resistance. Binder metals such as Cr and Ni were completely melted and WC was decomposed partially to W2C and graphite during the high temperature (up to 3500°C) thermal spraying. The melted metals were bonded with WC and other carbides and were formed as WC-metal coating. The graphite and excessively sprayed oxygen formed carbon oxide gases, and these gases formed porous coating by evolution of the gases. The surface properties were improved by HVOF coating and were improved further by CO2 laser heat treatment (LH). Wear resistance of In718 surface was improved by coating and LH at 25°C and an elevated temperature of 450°C, resulting in reduction of wear trace traces, and was further improved by LH of the coating in reducing wear depth. Corrosion resistance due to coating in sea water was improved by LH. HVOF coating of WC-metal powder on a metal surface and a LH of the coating were highly recommended for the improvement of In718 surface properties, the friction behavior, and wear resistance.